International perspectives and trends in research on inclusive education: a systematic review - Amor, Antonio M.; Hagiwara, Mayumi; Shogren, Karrie A.; Thompson, James R.; Verdugo, Miguel Ángel; Burke, Kathryn M.; Aguayo, Virginia (International journal of inclusive education, 2019)
Inclusive education of students with disabilities in general education contexts has been a global movement for at least 30 years. We completed a systematic review of articles published in English- and Spanish-language peer-reviewed journals to obtain an international perspective on the status of inclusive education research and practice regarding students with disabilities, as reflected in the literature from 2002 through 2016. Our literature search, which involved two parallel searches to compare and contrast articles published in the English and Spanish professional literature, yielded 2380 articles which were categorised into seven categories: theory, descriptive, attitudinal, literature review, intervention, and non-inclusive. For both the English and Spanish literature, the most two common article types were theory and descriptive. The number of intervention articles, with findings on the efficacy of interventions to promote inclusive practices, was drastically lower in the Spanish literature. Implications for advancing future research and practice are discussed.